2014
DOI: 10.1007/s00345-014-1371-9
|View full text |Cite
|
Sign up to set email alerts
|

Gleason underestimation is predicted by prostate biopsy core length

Abstract: While core length on trans-rectal biopsy independently affects Gleason upgrading on RP specimens, performer experience has minor impact on Gleason discordance or biopsy positivity due to a sharp learning curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
6
1
1
Order By: Relevance
“…Prostate core lengths has been correlated with GS underestimation risk. 39,40 Thus a better matching was obtained in increasing the number of core 41,42 and the prostate sampling volume. 43,44 Rapiti et al 24 found that the proportion of exact matching improved significantly when patients had ⩾ 10 cores compared with those who had ⩽ 9.…”
Section: Discussionmentioning
confidence: 93%
“…Prostate core lengths has been correlated with GS underestimation risk. 39,40 Thus a better matching was obtained in increasing the number of core 41,42 and the prostate sampling volume. 43,44 Rapiti et al 24 found that the proportion of exact matching improved significantly when patients had ⩾ 10 cores compared with those who had ⩽ 9.…”
Section: Discussionmentioning
confidence: 93%
“…All of cores biopsy were obtained in the same manner under the coordination of three experienced urologists of our Department. Reis et al (26) evaluated the clinical impact of the core length on the PCa diagnosis and pathologic upgrade in the setting of an experienced performer (>250 PBx/year) opposing to in-training urology residents. However, several limitations need to be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…), operator skill (e.g., learning curve etc. ), location and number of cores, core length ( 25 , 26 ). In our study, all of these parameters were similar in each group, except the core length which was not evaluated.…”
Section: Discussionmentioning
confidence: 99%